2022
DOI: 10.1590/fst.44021
|View full text |Cite
|
Sign up to set email alerts
|

Polygonatum sibiricum polysaccharide inhibits IL-1β-induced inflammation in human chondrocytes

Abstract: Osteoarthritis (OA) is a degenerative joint disease associated with inflammation. Polygonatum sibiricum polysaccharide (PSP) is a major group of active components isolated from Polygonatum sibiricum with broad activities including anti-inflammatory effect. However, the role of PSP in OA is unclear. In the present study, we aimed to investigate the effects of PSP on IL-1β-induced inflammatory response in primary human OA chondrocytes. The results showed that PSP improved cell viability of chondrocytes in respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…Following that, cartilage degradation and bone erosion occur over time because of MMP’s and cytokine release (IL-1β and TNF-α). A role for macrophages and their linked inflammatory cytokines in knee OA has also been identified [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Following that, cartilage degradation and bone erosion occur over time because of MMP’s and cytokine release (IL-1β and TNF-α). A role for macrophages and their linked inflammatory cytokines in knee OA has also been identified [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…6. During KOA progression, under stimulated conditions, in ammatory cytokines activate NF-κB, which upregulates COX-2 and iNOS expressions, and induces expressions of other proin ammatory cytokines, namely, IL-6, TNF-α, NO, and PGE2 [41]. Moreover, excess expression of the aforementioned proin ammatory cytokines induce upregulation of metalloproteinase-3 (MMP-3) [42].…”
Section: Discussionmentioning
confidence: 99%
“…The I κ B α is an important mechanism for the activation and repression of NF- κ B [ 35 ]. We found that GLA decreased the levels of p-p65 and suppressed the p65 accumulation in nucleus, which indicated that GLA prevented NF- κ B pathway activation [ 36 ].…”
Section: Discussionmentioning
confidence: 99%